Determination of specific LNAPL volumes in soils having a multimodal pore-size distribution - Alfaro Soto, Miguel A. [UNESP]; Lenhard, Robert; Chang, Hung K. [UNESP]; van Genuchten, Martinus Th [UNESP] (Elsevier, 2019)
In this paper we present modifications to previously published models for determining the specific volume of non-aqueous phase liquids (LNAPLs) in the subsurface at and near the groundwater table following a spill or leak from the soil surface. The modifications account for porous media having multimodal pore-size distributions as is often the case with tropical soils. Data from the literature are used to show that the use of multimodal pore-size distributions can lead to significantly different subsurface LNAPL specific volume predictions and possible LNAPL recovery rates, compared to when only unimodal pore-size distributions are considered. Differences of up to 200% are possible when the dual-porosity nature of the pore system is ignored, which can yield erroneous estimates of the time needed to remediate LNAPLs from contaminated areas when conventional systems are employed.
Keywords: Free LNAPL; LDRM; Multimodal pore systems; Recoverable LNAPL